Faktor-Faktor yang Mempengaruhi Accounting Fraud Pengelolaan Keuangan Desa di Kecamatan Sooko Kabupaten Mojokerto - Muhammad Fiqi Hendrawan; Junaidi Junaidi; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The present study examines the impact of openness, accountability, and community engagement on the quality of village financial reports within the Sooko sub-district, located in the Mojokerto district. This research focuses on a case study of the village apparatus responsible for overseeing the management of financial reports pertaining to the village and community. The village consultative body encompasses this apparatus. The research used a sample size of 75 respondents who satisfied the predetermined sample criteria, including 15 village head offices. This research used the approach of multiple linear regression analysis. The results of this study indicate that the variables of internal control effectiveness, organizational ethical culture, and observance of accounting rules have a significant effect on accounting fraud. While partially 1) internal control variables partially have a significant and positive effect on accounting fraud, 2) organizational ethical culture variables partially have a significant and positive effect on accounting fraud, 3) compliance with accounting rules partially has a significant and positive effect on accounting fraud.Keywords: Effectiveness of internal control, organizational ethical culture, observance of accounting rules, accounting fraud.